2016
DOI: 10.14198/jhse.2016.114.01
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and physiological analysis of the performance of the referee football and its relationship with decision making

Abstract: The aim of this study was to examine the cinematic and physiological requirements of referees and assistant referees and their relationship to decision-making in various official competition matches in football. The sample consisted of six referees, one acted as main referee and five as assistant referees (age: 21.2 ± 0.98 years; height: 175.67 ± 4.27 cm, weight: 65.73 ± 4.68 kg). The registration of the data of the subjects participating in the study was conducted with an inertial system called WIMU and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 8 publications
3
11
1
1
Order By: Relevance
“…In this case, referees spend ~80% of the game time in the walking and jogging (0–12 km/h) speed zone, which probably has matches with low intensity, depending on the game style and the characteristics of the competition, teams, and players. Instead, football referees perform movements below 12 km/h for 65% of the match [19]; these results are different because the distance covered in football is more than basketball. In both cases, similar time values exist in high intensity or sprint actions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this case, referees spend ~80% of the game time in the walking and jogging (0–12 km/h) speed zone, which probably has matches with low intensity, depending on the game style and the characteristics of the competition, teams, and players. Instead, football referees perform movements below 12 km/h for 65% of the match [19]; these results are different because the distance covered in football is more than basketball. In both cases, similar time values exist in high intensity or sprint actions.…”
Section: Discussionmentioning
confidence: 99%
“…The ranges of speed zones were: V 1 = 0–6 km/h (walking); V 2 = 6–12 km/h (jogging); V 3 = 12–18 km/h (running); and V 4 = 18–21 km/h (sprinting). These ranges of speed were established according to criteria developed by Gómez-Carmona and Pino-Ortega, [19] and based on the characteristic demands of basketball officiating.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the physiological demands and performance capabilities of soccer players have been extensively studied, 13 fewer studies have focused on soccer referees. 4,5 In one study, measurements of heart rate, blood lactate, and time–motion analyses in national league games showed that the referees had significant aerobic energy production throughout the game, as well as frequent episodes of anaerobic turnover. 6 Nevertheless, these investigators found that the referees’ ability to perform high-intensity running (HIR) was reduced toward the end of the match.…”
Section: Introductionmentioning
confidence: 99%